(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Electroencephalography (EEG) is a non-invasive technique used to record electrical activity of the brain. Since its invention in the early 20th century by Hans Berger, EEG has become an essential tool in neuroscience, clinical diagnostics, and brain-computer interface research. This article explores the structure of the EEG apparatus and its role in studying brain activity, detailing both technical and functional aspects of the technology. Understanding EEG: Basic Principles EEG measures voltage fluctuations resulting from ionic current flows within the neurons of the brain. These electrical signals are recorded from the scalp using electrodes and provide insights into brain functions such as sleep, attention, cognition, and even disorders like epilepsy and Alzheimer’s disease.